ΜPump: An open-source pressure pump for precision fluid handling in microfluidics. (April 2020) - Gao, Run Ze; Hébert, Marie; Huissoon, Jan; Ren, Carolyn L.
Graphical abstract: Abstract: An open-source precision pressure pump system and control software is presented, primarily designed for the experimental microfluidics community, although others may find additional uses for this precision pressure source. This mechatronic system is coined 'µPump, ' and its performance rivals that of commercially available systems, at a fraction of the cost. The pressure accuracy, stability, and resolution are 0.09%, 0.02%, and 0.02% of the full span, respectively. The settling time to reach 2 bar from zero and stabilize is less than 2 s. Material for building a four-channel µPump (approx. $3000 USD) or an eight-channel µPump (approx. $5000 USD) is approximately a quarter, or a third of the cost of buying a high-end commercial system, respectively. The design rationale is presented, together with documented design details and software, so that the system may be replicated or customized to particular applications. µPump can be used for two-phase droplet microfluidics, single-phase microfluidics, gaseous flow microfluidics and any other applications requiring precise fluid handling. µPump provides researchers, students, and startups with a cost-effective solution for precise fluid control.